Prevalencia de Toxocara canis en los parques del cantón Bolívar - Lerena Hidalgo, Paola Lizeth (2024)
The objective was to determine the prevalence of Toxocara canis in dogs found in public parks in Calceta, Membrillo and Quiroga parishes. The Shutter technique was applied to determine the presence of Toxocara canis, a survey of dog owners found in parks was carried out, and fecal samples were taken from 357 dogs. The study variables were: sex, age, breed, origin, origin, feeding, frequency of walking, place of walking, habitat, collection of feces and frequency of deworming. From these results, a prevalence of Toxocara canis was obtained in 229 (64.15%) positive cases and 128 negative cases (35.85%). It was determined that there is a higher prevalence of Toxocara canis in females with a total of 131 cases in the three areas already mentioned (65.94%), with respect to age it was determined that there is a higher infection in animals older than 12 months with 148 cases (64.63%), on the other hand, feeding with 129 cases (56.33%), corresponds to mixed food, then to the frequency of walking with a total of 134 dogs (58. Finally, the frequency of deworming with 117 cases (51.09%) with a semiannual deworming, finally, the infection was more common in females and in animals older than 12 months, also, a greater presence of Toxocara canis was observed in those dogs that consumed a mixed diet and those dogs with a semiannual deworming.